The Distribution of Intestinal Amoebae in Wild Long-Tailed Macaques (Macaca fascicularis) in Sabang City, Aceh Province, Indonesia - Junaidi, Junaidi; Cahyaningsih, Umi; Purnawarman, Trioso; Latif, Hadri; Sudarnika, Etih; Farida, Farida; Maryatun, Maryatun (Trends in Sciences, 2022)
Amoeba that infects primates can also be found in humans and can be zoonotic. This study aims to identify the distribution of intestinal amoeba in the wild Long-Tailed Macaque (LTM) group located at Cot Murong, Kebun Mangga, and Tugu Zero Kilometer Monument (IZKM) in Sabang City, Aceh Province, Indonesia. A total of 177 stool samples from 59 tails from the three LTM groups were examined microscopically. The results of the examination confirmed seven species of intestinal amoeba, three of which belonged to the genus Entamoeba, namely the Entamoeba histolytica/dispar/moshkovskii complex, Entamoeba coli, Entamoeba pölecki, and four other species from different genera, namely Iodamoeba butschlii, Blastocystis sp., Endolimax nana and Dientamoeba fragilis. The prevalence of intestinal amoeba in wild LTM in Sabang City was 57.6% (102/177). Dientamoeba fragilis was only found in the LTM group of Kebun Mangga. Entamoeba coli dominated the highest prevalence in all LTM groups. The LTM group located around Cot Murong and IZKM had a higher concentration of infection with intestinal amoeba than the Kebun Mangga location. The statistical tests showed a significant difference between the proportions of Iodamoeba butschlii, Endolimax nana and Dientamoeba fragilis, both found in the LTM Cot Murong, Kebun Mangga, or IZKM groups. This study is the first to report amoebic infection prevalence in the wild LTM group in Sabang City, Aceh Province. The pathogenic amoeba that cannot be distinguished microscopically from morphologically identical amoebae needs to be identified molecularly to identify variants and their potential as zoonotic agents. HIGHLIGHTS Intestinal amoeba species found in fecal samples of the wild long-tailed macaques group of Sabang City, Aceh Province, Indonesia, can also be found in human stool samples As many as three of the seven identified amoeba species, namely Entamoeba histolytica, Dientamoeba fragilis, and Blastocystis sp. is a pathogen that can cause diarrhea and colitis in humans and non-human primates The prevalence of amoeba infection in wild macaques in Sabang City is in the high category and tends to increase the incidence of infection in the macaque group, which has more susceptible individuals, namely infants, children, and females GRAPHICAL ABSTRACT